The Methods historical writing At European historians In the Age Crusades (Raparin Journal of Humanities (RJH), 2020)
The Eastern Islamic world was for a fairly long time under influence European campaigns one by one, which influenced the method of writing history at the Europeans in that era or later.One of the most dramatic phenomena of the medieval phenomena of elite appearance.      It is noticeable that a group of great historians with views and analysis of historical events, especially in the period of the Crusades when Europeans were writing against Muslims, especially in Egypt and Levant. At the beginning of these campaigns appeared many famous historians, where their writings receive attention from researchers      In  their writings, a large part of these events became the focus of the readers of generations that came after them.In this research we tried to shed light on the approach and accuracy of the ideas and opinions of these historians in addition to the extent of their credibility or bias or neutrality as historians.     This research divided into several sections. The first section highlights the method of writing the history of Europeans during the crusade. The second section deals with the methodology of writing history by European historians during the period of the first crusade to the fourth crusade. In the third section, the methodology of writing the history of European historians during the period of the fourth crusade was highlighted to the seventh Crusade. In the fourth section, the method of writing history was highlighted by European historians during the period of the seventh crusade.